2012
DOI: 10.1007/s11199-012-0255-y
|View full text |Cite
|
Sign up to set email alerts
|

Being a Body: Women’s Appearance Related Self-Views and their Dehumanization of Sexually Objectified Female Targets

Abstract: When sexually objectified, women are reduced to their bodies or sexual body parts and become likely targets of dehumanization. Not only men, but also women engage in this process. In the present research, we tested the link between women’s appearance related self-views and their tendency to dehumanize sexually objectified female targets. Specifically, we test two mediational models and predict that (1) women’s motivation to look attractive to men and (2) their tendency to internalize the sociocultural beauty s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 27 publications
(53 reference statements)
2
54
2
1
Order By: Relevance
“…Research shows that women can internalize messages of objectification reinforced through the objectifying gaze and use these messages to self-objectify. Moreover, women can also reproduce the objectifying gaze on other women, disciplining narrow ideals of female beauty, weight, appearance, and sexuality (Puvia & Vaes, 2013). In this way, as Rojek (1995) explained, "our behaviour is regulated by the gaze of others and by the gaze of our own-reflection" (p. 61).…”
Section: Women's Gossip and Reproductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research shows that women can internalize messages of objectification reinforced through the objectifying gaze and use these messages to self-objectify. Moreover, women can also reproduce the objectifying gaze on other women, disciplining narrow ideals of female beauty, weight, appearance, and sexuality (Puvia & Vaes, 2013). In this way, as Rojek (1995) explained, "our behaviour is regulated by the gaze of others and by the gaze of our own-reflection" (p. 61).…”
Section: Women's Gossip and Reproductionmentioning
confidence: 99%
“…This privilege gives men power to determine narrowly what defines female beauty. The objectifying gaze positions women as passive objects to be critiqued and objectified by men (Mulvey, 1975 can also see women as objects through the gaze (Puvia & Vaes, 2013). Research shows that women can internalize messages of objectification reinforced through the objectifying gaze and use these messages to self-objectify.…”
Section: Women's Gossip and Reproductionmentioning
confidence: 99%
“…Previous research has found that when women are sexualized, they are also often dehumanized (Bernard et al, 2015;Puvia & Vaes, 2013Vaes, Paladino, & Puvia, 2011). In addition, sexualization might have primed perceived humanness and agency.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
“…The result of research of Vaes et al (2011) has shown that both male and female participants attributed objectified women to lesser human characteristics compared to non-objectified women that the body less emphasized. Also, research of Puvia and Vaes (2013) has shown that sexually objectified women are significantly dehumanized while non-objectified women are not dehumanized.…”
Section: Introductionmentioning
confidence: 99%